The photography teacher's handbook : practical methods for engaging students in the flipped classroom - Horner, Garin (Photography Educators Ser., 2016)
The Photography Teacher's Handbookis an educator's resource for developing active, flipped learning environments in and out of the photo classroom, featuring ready-to-use methods to increase student engagement and motivation. Using the latest research on the cognitive science of effective learning, this book presents groundbreaking strategies to inspire students to collaborate, explore, and internalize photographic principles and concepts. The innovative practices in this book reimagine the traditional, scholarly pedagogy into a dynamic, teacher-guided, learner-centered approach.